Preparation of C60 Nanowhiskers-ZnS Nanocomposites and Photocatalytic Degradation of Methylene Blue - Soo Park, Hae; Bae Ko, Weon (Asian Journal of Chemistry, 2015)
Liquid-liquid interfacial precipitation (LLIP) method was used to prepare C60 nanowhiskers. Zinc sulfide nanoparticles were synthesized by zinc nitrate hexahydrate and thiourea under microwave irradiation. C60 nanowhiskers-ZnS nanocomposites were prepared by a reaction of C60 nanowhiskers and ZnS nanoparticles in an electric furnace. The C60 nanowhiskers-ZnS nanocomposites were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and UV-visible spectrophotometry. The C60 nanowhiskers-ZnS nanocomposites were evaluated as a photocatalyst in the photocatalytic degradation of methylene by UV-visible spectrophotometry under ultraviolet light at 254 nm.